Financing the Entrepreneurial Decision: An Empirical Approach Using Experimental Data on US High Technology Entrepreneurs - Elston,Julie; Audretsch,David B. (Small Business Economics, 2011)
This paper empirically examines the role of risk attitudes and wealth on financing choices for successful US entrepreneurs. Our approach uses both survey data and data from economics based field experiments, which enables us control for the risk attitudes of entrepreneurs. Empirical findings suggest that lower levels of wealth increase the probability of using a Small Business Innovation Research (SBIR) grant, but lower levels of wealth also reduce the probability of using loan financing. In addition results show that higher levels of risk aversion, but not wealth, increase the probability of financing firm start-ups with earnings from a second job. Overall, findings suggest that both wealth and risk attitudes may play an important role in the financing choice of entrepreneurs.
Keywords: Finance; OSU-Cascades